2011
DOI: 10.1002/qua.22746
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase acylium ion transfer reactions mediated by a proton shuttle mechanism

Abstract: ABSTRACT:The mechanism and the energy profile of the gas-phase reaction that mimics esterification under acidic conditions have been investigated at different levels of theory. These reactions are known to proceed with rate constants close to the collision limit in the gas-phase and questions have been raised as to whether the typical addition-elimination mechanism via a tetrahedral intermediate can explain the ease of these processes. Because these reactions are common to many organic and biochemical processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…It does have a stable entrance channel complex, however, and the vibrational mode with an imaginary frequency at the transition state is essentially a single hydrogen atom motion (reduced mass 1.09 u), meaning that if the complex were collisionally or radiatively stabilized, protonated methyl formate could be formed via tunneling. , (2) This reaction also requires a large abundance of protonated formic acid, but H 3 + , which plays a central role in interstellar ion–molecule chemistry, cannot protonate formic acid directly, as this reaction instead results in molecular dissociation. , Instead, protonation of formic acid must occur by another ion, such as HCO + or H 3 O + , either of which has been shown in the laboratory to efficiently form this ion. (3) Proton transfer between the reactants is exothermic and may be more facile; two studies found that this proton transfer pathway is the dominant reaction channel. , (4) It has also been suggested that the gas-phase esterification reaction does not proceed through the traditional Fischer mechanism, with a tetrahedral intermediate. A recent study suggests that a closely related reaction, that of protonated acetic acid and methanol, may instead proceed through a proton-shuttling mechanism and might not have a reaction barrier. Due to the complexity of this pathway, the authors were unable to determine the complete reaction path; additional calculations are needed to determine whether acid-catalyzed Fischer esterification is a viable alternative mechanism to produce interstellar methyl formate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It does have a stable entrance channel complex, however, and the vibrational mode with an imaginary frequency at the transition state is essentially a single hydrogen atom motion (reduced mass 1.09 u), meaning that if the complex were collisionally or radiatively stabilized, protonated methyl formate could be formed via tunneling. , (2) This reaction also requires a large abundance of protonated formic acid, but H 3 + , which plays a central role in interstellar ion–molecule chemistry, cannot protonate formic acid directly, as this reaction instead results in molecular dissociation. , Instead, protonation of formic acid must occur by another ion, such as HCO + or H 3 O + , either of which has been shown in the laboratory to efficiently form this ion. (3) Proton transfer between the reactants is exothermic and may be more facile; two studies found that this proton transfer pathway is the dominant reaction channel. , (4) It has also been suggested that the gas-phase esterification reaction does not proceed through the traditional Fischer mechanism, with a tetrahedral intermediate. A recent study suggests that a closely related reaction, that of protonated acetic acid and methanol, may instead proceed through a proton-shuttling mechanism and might not have a reaction barrier. Due to the complexity of this pathway, the authors were unable to determine the complete reaction path; additional calculations are needed to determine whether acid-catalyzed Fischer esterification is a viable alternative mechanism to produce interstellar methyl formate.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 (4) It has also been suggested that the gasphase esterification reaction does not proceed through the traditional Fischer mechanism, with a tetrahedral intermediate. A recent study 44 suggests that a closely related reaction, that of protonated acetic acid and methanol, may instead proceed through a proton-shuttling mechanism and might not have a reaction barrier. Due to the complexity of this pathway, the authors were unable to determine the complete reaction path; additional calculations are needed to determine whether acidcatalyzed Fischer esterification is a viable alternative mechanism to produce interstellar methyl formate.…”
Section: Interpretation Of Chemical Images Based On Chemicalmentioning
confidence: 99%
“…The protonated monomer of AA has previously been studied using ab initio calculations and mass spectrometry. However, despite it being a rather fundamental organic cation, no optical spectra have been reported for it or for the monomer of other simple protonated carboxylic acids, (RCOOH)­H + . Inokuchi and Nishi have measured infrared (IR) photodissociation spectra in the OH stretching region for protonated formic acid cluster ions, (HCOOH) n H + , and their AA analogues, for n ≥ 2 .…”
mentioning
confidence: 99%